Unregulated and regulated free banking: The case of Switzerland reinterpreted - Nils Herger (Swiss National Bank, Study Center Gerzensee, 2019)
The free-banking history of Switzerland is commonly subdivided into a period with unfettered competition (1826 - 1881) and strong banknote regulation (1881 - 1907). This paper suggests that unrestricted competition between private note-issuing banks gave rise to a fragmented paper-money system, which suffered from a lack of standard- ised, and commonly accepted, banknotes. Minimum-reserve requirements and mutual- acceptance rules were introduced to standardise banknotes. Rather than overissuing, these regulatory interventions restricted the exibility (or "elasticity") of the paper-money supply. It turned out that a central note-issuing bank was needed to supply adequate amounts of standardised banknotes.
Keywords: E42; N14; N23; 330; central bank; free banking; note-issuing bank; Switzerland